Evidence of pre-micellar aggregates in aqueous solution of amphiphilic PDMS–PEO block copolymer. Issue 22 (28th May 2019) - Lombardo, Domenico; Munaò, Gianmarco; Calandra, Pietro; Pasqua, Luigi; Caccamo, Maria Teresa
Abstract : The decrease in the PEO chain hydration favours the increase in the PDMS–PEO micelle aggregation number with the increase in temperature. Abstract : The self-assembly process in a water solution of an amphiphilic polydimethylsiloxane- b -polyethyleneoxide (PDMS–PEO) diblock copolymer was investigated by means of small-angle X-ray scattering (SAXS) experiments in the concentration region below (and near) the critical micellar concentration (c.m.c. = 0.007 g cm −3 ). In the highly diluted region, at the copolymer concentration of c = 0.002 g cm −3, the early stage of the self-assembly process was characterized by the formation of small (primary) micellar units (with a radius of R = 2.7 nm) with core–shell morphology, which coexisted with larger supramolecular aggregates of entangled micelles (with an average radius of R = 9.5 nm). The increase in the copolymer concentration (to c = 0.005 and c = 0.01 g cm −3 ) caused increase in the sizes of both the small micelles and supra-micellar aggregates. Interestingly, at the concentration of c = 0.005 g cm −3, both the size and micelle aggregation number ( N agg ) were found to increase on increasing the temperature in the range of 10 ≤ T ≤ 55 °C. This phenomenon was characterised by the dehydration process of the ethylene oxide (EO) segments, as evidenced by the calculation of excess water in the hydrophilic shell of the micelles. The more compact (less hydrated) structure of the hydrophilic PEO chains, which strongly influenced the spontaneous curvature of the amphiphile hydrophilic region, turned out to be the driving factor that favoured the increase in the micelle aggregation number with the increase in temperature. The obtained results evidence that the self-assembly process of PDMS–PEO copolymer amphiphiles is a gradual process that is already present at the very low concentration region (far below the macroscopically determined c.m.c.); moreover, it is characterised by a multi-stage organization process, where the primary building blocks self-assemble into more complex secondary structures that encompass multiple length scales.